Testing Conditional Convergence of Growth Under Mankiw-Romer-Weil's Test of Neoclassical Growth Model - Cader, Mohamed (2014)
Solow’s neoclassical growth model predicts that countries with low capital stock tend to converge to their steady-state at a faster rate. This study attempts to test conditional convergence of GCC economies. The study finds significant empirical evidence of conditional convergence of the GCC economies over the period from 1971 to 2011 using the Mankiw et al. (1992) model. Using panel data estimation, the study estimates savings and population growth rates and their effects on income per capita in GCC economies. The results indicate significant negative relationship between domestic investment and output per capita due to net capital outflows. Capital inflows appear to be insufficient to offset the large investments by GCC governments abroad. A positive relationship between output per capita income and employment growth is found and is inconsistent with Solow’s growth model predictions. Wage elasticity in estimation of conditional convergence supports the hypothesis that GCC economies grow in output per capita due to growth in government expenditure. Results found wages to have a positive relationship with income per capita. GCC economies tend to increase their welfare programs and wages as their output per capita grows. Due to the inadequate macroeconomic policies in GCC economies, estimation finds profits to have a negative relationship with income per capita, which is also inconsistent with Solow’s predictions. It is believed to be attributed to GCC governments’ generous welfare programs which tend to lower interest rates, thus lowering investments and profits. Speed of convergence for GCC economies is found to be a positive 0.219 which is attributed to net capital outflows of GCC economies, hindering growth of investments